THE EFFECT OF FILMS WITH DIFFERENT PROPERTIES ON THE BIOLOGICAL CHANGES IN THE LEAVES OF STRAWBERRY VARIETIES IN GREENHOUSE CONDITIONS (Scientific journal of the Fergana State University, 2025)
Strawberries grown in greenhouse conditions on PO and PE films differed from each other in terms of genetic characteristics and characteristics of the varieties. Genetic characteristics can be formed during any phase of plant growth or development. "Kings Berry" has the largest leaf area, which indicates its strong vegetative growth potential. Also, in the initial phase, "Jukhyang" and "Maehyang" varieties have the ability to use light effectively. Therefore, we came to the conclusion that the possibility of sharp physiological-biochemical changes in these varieties will change.